Fragile New Economy: Intangible Capital, Corporate Savings Glut, and Financial Instability - Li, Ye (American Economic Review, 2025)
The transition toward an intangible-intensive economy reshapes financial systems by creating a self-perpetuating savings glut in the production sector. As intangibles become increasingly important, firms hoard liquidity to finance investment in intangibles of limited pledgeability. Firms’ savings feed cheap leverage to financial intermediaries and allow intermediaries to bid up asset prices, which in turn encourages firms to save more for asset creation. This paper develops a macrofinance model that offers a coherent account of rising corporate savings, debt-fueled growth of intermediaries, declining interest rates, and rising asset valuation. Along these secular trends, endogenous financial risk accumulates. (JEL E43, E44, G12, G21, G31, G32)